Oncological Outcomes After Robotic Proctectomy for Rectal Cancer: Analysis of a Prospective Database. Issue 3 (March 2018) - Sammour, Tarik; Malakorn, Songphol; Bednarski, Brian K.; Kaur, Harmeet; Shin, Ui Sup; Messick, Craig; You, Yi-Qian Nancy; Chang, George J.
Abstract : Objective: The aim of this study is to evaluate the oncological outcomes of robotic total mesorectal excision (TME) at an NCI designated cancer center. Summary Background Data: The effectiveness of laparoscopic TME could not be established, but the robotic-assisted approach may hold some promise, with improved visualization and ergonomics for pelvic dissection. Oncological outcome data is presently lacking. Methods: Patients who underwent total mesorectal excision or tumor-specific mesorectal excision for rectal cancer between April 2009 and April 2016 via a robotic approach were identified from a prospective single-institution database. The circumferential resection margin (CRM), distal resection margin, and TME completeness rates were determined. Kaplan–Meier analysis of disease-free survival and overall survival was performed for all patients treated with curative intent. Results: A total of 276 patients underwent robotic proctectomy during the study period. Robotic surgery was performed initially by 1 surgeon with 3 additional surgeons progressively transitioning from open to robotic during the study period with annual increase in the total number of cases performed robotically. Seven patients had involved circumferential resection margins (2.5%), and there were no positive distal or proximal resection margins. One hundred eighty-six patients had TME quality assessed, and only 1 patient (0.5%) had an incomplete TME. Eighty-three patients were followed up for a minimum of 3 years, with a local recurrence rate of 2.4%, and a distant recurrence rate of 16.9%. Five-year disease-free survival on Kaplan–Meier analysis was 82%, and 5-year overall survival was 87%. Conclusions: Robotic proctectomy for rectal cancer can be performed with good short and medium term oncological outcomes in selected patients.